On some colorful bryozoans from Brazil: reevaluation of Aptonella violacea Canu & Bassler, 1928 and a new species of Cosciniopsis Canu & Bassler, 1927 - Larré, Igor R.n.m.; Almeida, Ana C.s.; Vieira, Leandro M. (Zootaxa, 2024)
Gigantoporidae Bassler, 1935 is a cheilostome bryozoan family comprising five genera, including the colorful genus Cosciniopsis Canu & Bassler, 1927, considered a senior synonym of Aptonella Canu & Bassler, 1928. The taxonomy of Aptonella has historically been considered confusing due to the colored zooecia, which suggests an affinity with other genera such as the stomachetosellid Cycloperiella Canu & Bassler, 1923. Here, the type species of Aptonella, A. violacea Canu & Bassler, 1928, is reevaluated and compared with other Gigantoporidae, to provide a new combination: Cycloperiella violacea n. comb. For the reassessment of Gigantoporidae, the type species of Gigantopora Ridley, 1881, G. lyncoides Ridley, 1881 is redescribed, and a new species of Cosciniopsis, C. viridis sp. nov. is described from Brazil. Characteristics of Cy. violacea, including a double calcified ooecium (lepralielliform type) and the acleithral-type aperture in ovicelled zooids, are distinct from other Gigantoporidae. This distinction supports the synonymization of Aptonella with Cycloperiella, which is here transferred to the family Bitectiporidae MacGillivray, 1895.